2022
DOI: 10.3389/fclim.2022.864292
|View full text |Cite
|
Sign up to set email alerts
|

The Politics of Governing Resilience: Gendered Dimensions of Climate-Smart Agriculture in Kenya

Abstract: This paper uses climate-smart agriculture (CSA) in Kenya as an empirical entry point for investigating how climate actions reshape or reinforce gender relations, and how they are aimed at improving local resilience that is nested in such relations. While enhancing national food security, CSA practices could however reproduce inequitable power relations, such as gendered authority relations that produce vulnerability and inequalities. Equity and knowledge represent particularly contested aspects of CSA because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 45 publications
2
4
0
Order By: Relevance
“…However, our review found no instances of external CCA interventions leading to such positive transformations. Hence, given that Climate-Smart Agriculture tends to be promoted by stakeholders that are external to households and communities, [7] our findings could in fact be considered as being in alignment as those of Brisebois et al concerning CSA adoption in Kenya [7].…”
Section: Intra-household Cca Dynamics and Gender Transformationsupporting
confidence: 76%
See 3 more Smart Citations
“…However, our review found no instances of external CCA interventions leading to such positive transformations. Hence, given that Climate-Smart Agriculture tends to be promoted by stakeholders that are external to households and communities, [7] our findings could in fact be considered as being in alignment as those of Brisebois et al concerning CSA adoption in Kenya [7].…”
Section: Intra-household Cca Dynamics and Gender Transformationsupporting
confidence: 76%
“…At first glance, this wide range of adaptive responses appears to deviate from the findings of a recent review concerning "gendered dimensions of Climate-Smart Agriculture in Kenya" [7, p.1], which found that decision-making about Climate Smart Agriculture consistently reinforced inequitable gender norms and roles. [7] While our findings do indicate that CCA might reinforce inequities in many instances, we have also found evidence of autonomous CCA processes that appeared to open up spaces for transformative re-negotiation. However, our review found no instances of external CCA interventions leading to such positive transformations.…”
Section: Intra-household Cca Dynamics and Gender Transformationmentioning
confidence: 43%
See 2 more Smart Citations
“…In this discussion, we engage particularly with two literature reviews concerning the gendered nature of CCA practices within rural East African households that were published while we were conducting our review. [7,8] While neither of these articles focus primarily on CCA decision-making, their findings are adjacent to the issues studied in the present review.…”
Section: Discussionmentioning
confidence: 95%